A Day By the Beach - Reimagining Coastal Tourism in the Age of Climate Change, Sri Lanka - Hellmark,Frida (2025)
As climate change accelerates, rising sea levels and eroding shorelines are reshaping our coastal landscapes. Short-term fixes, such as beach nourishment and offshore breakwaters, are proving increasingly ineffective and costly. In nations like Sri Lanka, where tourism is a vital pillar of the economy and heavily dependent on beaches, these transient measures have become financially unsustainable. The escalating impacts of climate change demand a shift towards long-term, resilient strategies. This project, situated in Hiriketiya, Sri Lanka, envisions a future where the concept of “a day by the beach” evolves, as long sandy beaches become increasingly unfeasible. The project explores adaptive designs that blend ecological restoration with recreational spaces, ensuring vibrant and sustainable coastal tourism in the face of climate challenges.
Keywords: Climate change; rising sea levels; eroding beaches; resilient strategies; adaptive designs; ecological restoration; recreational spaces; sustainable coastal tourism; Hiriketiya; Sri Lanka.